Copper as a key regulator of cell signalling pathways. (22nd May 2014) - Grubman, Alexandra; White, Anthony R.
Abstract : Copper is an essential element in many biological processes. The critical functions associated with copper have resulted from evolutionary harnessing of its potent redox activity. This same property also places copper in a unique role as a key modulator of cell signal transduction pathways. These pathways are the complex sequence of molecular interactions that drive all cellular mechanisms and are often associated with the interplay of key enzymes including kinases and phosphatases but also including intracellular changes in pools of smaller molecules. A growing body of evidence is beginning to delineate the how, when and where of copper-mediated control over cell signal transduction. This has been driven by research demonstrating critical changes to copper homeostasis in many disorders including cancer and neurodegeneration and therapeutic potential through control of disease-associated cell signalling changes by modulation of copper–protein interactions. This timely review brings together for the first time the diverse actions of copper as a key regulator of cell signalling pathways and discusses the potential strategies for controlling disease-associated signalling processes using copper modulators. It is hoped that this review will provide a valuable insight into copper as a key signal regulator and stimulate further research to promote our understanding of copper in disease and therapy.